2022
DOI: 10.1039/d2qi00265e
|View full text |Cite
|
Sign up to set email alerts
|

Nickel ferrocyanides for aqueous ammonium ion batteries

Abstract: In this report, we design a structural optimization in Ni2Fe(CN)6 through a partial substitution of nickel by sodium, and investigate the electrochemical performance of a series of Na2xNi2-xFe(CN)6 (x =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…On the other hand, compared with the previously developed cathodes (metal-organic PBAs and some organic compounds) with stable discharge plateau, our VOPO 4 •2H 2 O cathode delivers a superior speci c capacity as shown in Fig. 2f [30][31][32][33][34][35][36][37][38][39][40] . The combination of stable charge/discharge potential plateau and high speci c capacity makes this material more appealing compared with the various conventional cathode materials.…”
Section: Resultsmentioning
confidence: 90%
“…On the other hand, compared with the previously developed cathodes (metal-organic PBAs and some organic compounds) with stable discharge plateau, our VOPO 4 •2H 2 O cathode delivers a superior speci c capacity as shown in Fig. 2f [30][31][32][33][34][35][36][37][38][39][40] . The combination of stable charge/discharge potential plateau and high speci c capacity makes this material more appealing compared with the various conventional cathode materials.…”
Section: Resultsmentioning
confidence: 90%
“…Wang et al used Na + to replace Ni + in Ni 2 Fe(CN) 6 partially, and the structure was gradually changed from the cubic phase to the rhombic phase. 121 The XRD spectrum can show this phenomenon as in Fig. 13e, where the appearance of splitting of (220), (420), and (440) diffraction peaks indicates the presence of two phases.…”
Section: Design Of Practical Electrode Materialsmentioning
confidence: 85%
“…Most recently, Na doping to optimize the electrochemical performance of Na 2x Ni 2À x Fe-(CN) 6 has been applied. [109] It is found that nickel ferrocyanide after a partial substitution of nickel with sodium (Na 1.5 Ni 1.25 Fe(CN) 6 ) can increase its working voltage and thus improve the reversible capacity to 56.1 mAh g À 1 after 150 cycles. Besides, the pre-insertion is demonstrated to be an effective strategy in battery systems, [110][111][112] which can enhance the structural stability and ionic conductivity, thus accelerating the diffusion of NH 4…”
Section: Intercalation-type Hosts With 3d Diffusion Channelsmentioning
confidence: 99%
“…reported well‐dispersed NaFe[Fe(CN) 6 ] nanocubes with an edge length of 500 nm as the NH 4 + host for AIBs, [102] maintaining 78 % of initial capacity after 50 000 cycles. Most recently, Na doping to optimize the electrochemical performance of Na 2x Ni 2−x Fe(CN) 6 has been applied [109] . It is found that nickel ferrocyanide after a partial substitution of nickel with sodium (Na 1.5 Ni 1.25 Fe(CN) 6 ) can increase its working voltage and thus improve the reversible capacity to 56.1 mAh g −1 after 150 cycles.…”
Section: Electrode Materials For Aibsmentioning
confidence: 99%